The Echocardiographic Spectrum of Atrial Myxoma: A Ten-Year Experience - Pechacek, Leonard W. (1986)
We analyzed the echocardiograms of 28 patients with a left atrial myxoma and two with a right atrial myxoma. Our purpose was to evaluate the value of echocardiography for the diagnosis of these cardiac masses. Only 59% of the m-mode echocardiograms in patients with a left atrial myxoma showed the characteristic findings of multiple diastolic echoes within the mitral orifice as well as abnormal systolic echoes within the left atrium. M-mode echocardiograms were atypical for left atrial myxoma in the remaining patients, and a definitive diagnosis could not be established on the basis of this procedure in six of the patients (22%). Two-dimensional echocardiography showed the presence of a left atrial mass in all 16 patients who had the procedure, and aided in understanding the atypical m-mode recordings. There was a close relationship (r = .82) between two-dimensional echocardiographic measurements of the myxomas' size and pathologic measurements. Both right atrial myxomas could be identified on the m-mode echocardiogram. Our experience indicates that two-dimensional echocardiography is superior to the m-mode technique for the diagnosis and characterization of left atrial myxomas.